Arabic language speaking anxiety among university students in Central Java - Anandi, Rizki Parahita; Muhammad Azhar Zailaini, (Penerbit Universiti Kebangsaan Malaysia, 2023)
This survey research identifies the students’ level of Arabic language speaking anxiety and determines any significant difference in their speaking anxiety based on their background. 322 Arabic language students from six State Islamic Universities in Central Java purposively participated in this study. The data was obtained using the Foreign Language Speaking Anxiety Scale (FLSAS). The data were analysed using Winstep version 3.73 from Rasch model and IBM SPSS version 23. The logit measure and the Wright map indicated that most students experienced moderate speaking anxiety, meaning they felt anxious only in some situations in the muhadathah class. In other words, their maturity (age) controls their anxiety. The independent sample t-test result indicated that their speaking anxiety varied regarding gender and previous experience in learning muhadathah, while their origin did not significantly affect their speaking anxiety. The one-way ANOVA test showed that mothers’ education level significantly affects the students’ speaking anxiety. The higher their mothers’ education level, the lower the speaking anxiety they experience.